Dewali Ancestral Worship and Social Cohesion among the Khabatari Budhathoki Lineage in Eastern Nepal - Budhathoki, Drona (International Research Journal of MMC, 2026)
Dewali is a traditional ancestral worship in Nepali communities where families honor lineage deities for protection, prosperity, and harmony. Rooted in indigenous beliefs, it strengthens kinship, preserves cultural values, and promotes social unity, continuity, and collective identity across generations within changing socio-cultural contexts. The Khabatari Budhathoki Chhetri, a lineage subgroup of the broader Chhetri community, historically held influential roles in Nepal’s administration and military. The chief objective of this study is to explore how Dewali ancestral worship shapes kinship relations and social cohesion among the Khabatari Budhathoki lineage in Eastern Nepal using an ethnographic and descriptive approach to examine the socio-cultural dynamics of the Khabatari Budhathoki community, focusing on Kul Puja (Dewali) as a key ancestral ritual. Primary data were collected from five purposively selected respondents through semi-structured interviews and participant observation conducted in Mulkharka, Dhankuta. The study analyzes lineage structure, ancestral worship, social participation, and everyday cultural practices. The study findings show that the Khabatari Budhathoki community preserves its genealogical identity through oral traditions, written genealogy, and Kul Puja practices. Dewali rituals strengthen lineage unity, kinship solidarity, cultural continuity, social cohesion, and collective responsibility, while faith in the Kul Devata shapes the community’s spiritual and social life. This study is useful for those who wish to understand the rituals, kinship structure, and social unity within the Khabatari Budhathoki lineage.